'Adjacent worlds': An analysis of a genre at the intersection of academic and professional communities. Issue 22 (June 2016) - Morton, Janne
Abstract: Two concepts – genre and discourse community – have been at the core of discussions about language and learning within the disciplines since John Swales integrated the two into ESP pedagogy. While in his earlier work, Swales (1990) proposed a relationship of genres 'belonging' to discourse communities, he later (e.g. 1998) understood discourse communities as sometimes cohering around genres, suggesting a more open-ended relationship between the concepts. This paper takes up the issue of this relationship, and reports on a recurrent event in architecture education. The data is drawn from a project on postgraduate design studio pedagogy at a major Australian university. The focus was the weekly activities in a studio taught by a senior academic. Working primarily within a rhetorical genre framework, this paper explores the desk-crit genre from two angles – its evolution over time and its performance in a contemporary studio session. The paper shows how a 'situated genre analysis' contributes to an understanding of the interconnections, tensions, different discourses of the academic and professional architecture communities, characterized in this paper as 'adjacent worlds'. The paper concludes that this type of analysis helps us understand genre as a space in which multiple discourse communities interact. Highlights: The academy and the profession in architecture education are 'Adjacent worlds'. A situated genre analysis can enrich our understanding of genre-community relations. Genre as a space in which multiple discourse communities interact. Guided reflection helps students negotiate genre variability across design studios.